A cross-sectional study on co-infection of hepatitis B and hepatitis C among people living with HIV/AIDS from a tertiary care hospital of Central India - Riddhi Pradhan; Kirti Hemwani; Vidit Khandelwal; Bamboriya BL; Yogyata Marothi; Varsha Saxena (Asian Journal of Medical Sciences, 2023)
Background: Hepatitis B virus (HBV), hepatitis C virus (HCV), and Human immunodeficiency virus (HIV) infections are prevalent throughout the world. HIV infection increases the risk of HBV and HCV liver disease especially when HIV-associated immunodeficiency progresses. Aims and Objectives: This study was carried out with the objectives as follows: Estimation of the prevalence of HIV- Hepatitis co-infection, determine CD4+T lymphocyte count in co-infected patients, identify most common opportunistic infections in HIV – Hepatitis co- infection. Materials and Methods: A hospital-based, prospective, cross-sectional, and observational study was carried among people with confirmed HIV infection. HIV antibody, hepatitis B surface antigen (HBsAg), and HCV antibody tests were done in all patients visiting to integrated counseling and testing center. HIV, HBV, and HCV viral load were done in all serologically confirmed patients. In HBsAg positive patients various markers for hepatitis such as hepatitis B envelop antigen (HBeAg), anti-hepatitis B core antibody (HBcAb), and anti-hepatitis B envelop antibody were also done. Results: Out of 357 people living with HIV/AIDS (PLHA) patients 15/357 (4.20%) were co-infected with HBV, 03/357 (0.84%) were co-infected with HCV. The overall seroprevalence of Hepatitis virus (HBV+HCV) in PLHA patients was found to be 5.04% (18/357). CD4+T lymphocyte count <200 cells/μL was seen in 66/339 (19.4%), 04/15 (26.6%), and 03/03 (100%) patients of HIV mono-infected, HBV co-infected, and in HCV co-infected patients, respectively. HIV Viral load ≤1000 copies/mL was seen in 324 and 15 patients in HIV mono-infected and HIV- hepatitis co-infected patient, respectively. Among PLHA patients who were positive for HBsAg; 46.7% (n=7) patients had HBV viral load >2000 IU/mL. All hepatitis B co-infected patients were positive for HBcAb test; HBeAg was positive in 40% (n=06). All HBeAg positive were having viral load >2000 IU/mL. Conclusion: HIV-infected patients are more prone to hepatitis associated liver diseases and exposure to the HBV infection than the general population.